80 Assessment of a novel integrated training programme in tranthoracic echocardiography for junior cardiac physiologists in a regional cardiac centre. (4th June 2021) - O'Toole, Laurence; Mackay, Jane; Fent, Graham; Watson, Oliver
Abstract : Introduction: There is a national shortage of sonographers trained to British Society of Echo (BSE) transthoracic echocardiography (TTE) accreditation standard, which impacts directly on safe patient care. TTE training is arduous and impacts on departmental output, and 30% of echo departments in England had no cardiac physiologists training in TTE in 2018. In the face of a waiting list crisis due to loss of accredited staff, we introduced a novel, multifaceted and integrated TTE training programme for Agenda for Change (AfC) band 5 cardiac physiologists in January 2018. The aim was to train these much more junior staff, who were largely naïve to echo, to BSE accreditation standard at twice our previous rate. Methods: The training programme included (i) a foundation course with selection for further training on the basis of competence, (ii) an introductory scanning module, (iii) pathology-specific training lists, (iv) training lists booked at reduced capacity (4 not 6 patients per list), (v) a complementary lecture programme, (vi) four levels of supervision with directions for both trainees and trainers of goals each week and (vii) on-going review of progress. The primary end-point was the number of trainees per year achieving BSE accreditation standard compared to a historical control group (January 2010 to January 2018) in our hospitals. Secondary end-points include the impact of the training programme on departmental capacity and the duration of training. Results: In the control period, 7 sonographers were trained to BSE accreditation in a mean of 31 months (range 24 to 48 months), a training rate of 1.0 accredited sonographer/year. These staff were all AfC band 6, began training at an average age of 30 years, had a median of 4.7 years of prior postgraduate experience in cardiac physiology (range 0.75 to 5.25 years), and 4 had past echo training experience elsewhere. From January 2018 to Jan 2021, 11 physiologists entered the new training programme. These trainees were an average age of 25 years, median AfC Band of 5.0 and had a median of 1.5 years (range 0.25 to 11 yrs) of postgraduate experience in cardiac physiology. The training programme reduced departmental core echo capacity by 16% in the second year of implementation. Core capacity was recovered in the third year as trainees completed the programme. TTE out-patient waiting lists were maintained at less than 6 weeks by support from out-of-hours' work. Four trainees did not complete the programme. Five physiologists achieved full BSE accreditation by January 2021, in an average of 27 months of training (range 22 to 34 months) with some delays due to the 2020 Covid pandemic. This represents a training rate to independent scanning of 1.7 sonographers per year on the new programme. Conclusion: A programme of intensive training of echo-naïve very junior cardiac physiologists achieved a 70% increase in the rate of attainment of BSE accreditation compared to historical performance with training completed in a similar timescale. This level of performance exceeds the need outlined in the 2015 strategic review of cardiac physiologist training. Conflict of Interest: None